2014
DOI: 10.18172/cig.2510
|View full text |Cite
|
Sign up to set email alerts
|

Evolución de la dinámica vegetal mediante una serie de imágenes Landsat TM(1986-2011): región central de Chihuahua, México

Abstract: RESUMEN. En este trabajo se ha analizado la evolución temporal y espacial de la dinámica vegetal sobre varias coberturas de suelo en la cuenca de la Laguna Bustillos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
2
0
2
Order By: Relevance
“…Al igual que en el presente estudio, Alatorre et al (2014) identificaron una tendencia de incremento en los valores del NDVI a partir del mismo sensor en el estado de Chihuahua en un análisis multitemporal (1986 -2011). genus level or, if they exist at the species level, which have as input the values of the diameter and height variables, which were generated by several authors (Návar, 2009;Rodríguez et al, 2006;Rodríguez et al, 2007;Rojas et al, 2015) for similar regions.…”
Section: Resultados Y Discusiónmentioning
confidence: 75%
See 1 more Smart Citation
“…Al igual que en el presente estudio, Alatorre et al (2014) identificaron una tendencia de incremento en los valores del NDVI a partir del mismo sensor en el estado de Chihuahua en un análisis multitemporal (1986 -2011). genus level or, if they exist at the species level, which have as input the values of the diameter and height variables, which were generated by several authors (Návar, 2009;Rodríguez et al, 2006;Rodríguez et al, 2007;Rojas et al, 2015) for similar regions.…”
Section: Resultados Y Discusiónmentioning
confidence: 75%
“…As in the actual study, Alatorre et al (2014) found a tendency of increase in the NDVI numbers from the same sensor in La distribución espacial de los conglomerados de muestreo utilizados tanto para la modelación (punto) como la validación (triángulo) se muestran en la Figura 3. En ellos se registraron 28 géneros y 66 especies arbóreas: Quercus con 22 especies fue el mejor representado, seguido de Pinus con nueve especies;…”
Section: Resultsunclassified
“…Así, la utilización de un recurso natural como el agua ha contribuido a la destrucción de los ecosistemas. Igualmente, la existencia de condiciones topográficas favorables (pendientes suaves) ha facilitado el desarrollo de cultivos hortícolas y de cereales en el tramo inferior del río Portoviejo, coincidiendo con lo que señalan Alatorre et al (2014) en un estudio de la dinámica vegetal en la región central de Chihuahua, México.…”
Section: Comportamiento Temporal Y Espacial Del Bosque Ribereño En Elunclassified
“…The detailed organization of plant cover explains the occurrence (or absence) of erosion processes in hillslopes, and the connectivity with fluvial channels. Cooperation between geomorphologists and ecologists could contribute to better understand the evolution of patchy vegetation (Thornes, 1990;Gallart et al, 1993;Valentin et al, 1999;Kefi et al, 2007), and to the identification of early warning signs of critical transitions or catastrophic shifts (Scheffer et al, 2009;Alfieri et al, 2012;Valiente-Banuet and Verdú, 2013;Alatorre et al, 2014). Similarly, studies on the resistance and resilience of vegetation to droughts, extreme rainfall events, fire and overgrazing are crucial for the control of soil erosion and transport.…”
Section: (Photo 4)mentioning
confidence: 99%